2010
DOI: 10.1016/j.juro.2009.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Dysfunction and Altered Somatic Sensitivity in PACAP −/− Mice

Abstract: Purpose Pituitary adenylate cyclase activating polypeptide (PACAP) and receptors are expressed in micturition pathways. Studies demonstrated roles for PACAP in detrusor smooth muscle contraction, facilitating ATP release from urothelium and PACAP antagonism reduced cyclophosphamide-induced bladder hyperreflexia. Materials and Methods PACAP contributions to micturition and somatic sensation were studied in PACAP knockout (PACAP−/−), littermate heterozygote (PACAP+/−) and wildtype (WT) mice using conscious cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Similarly, increases in peripheral sensitivity to mechanical stimuli using von Frey filament application to the hindpaw are seen following CYP-induced cystitis in rodents (73). Therefore, increases in hindpaw and pelvic referred somatic sensitivity in the present study are similar to results seen in animal models of IC/BPS (45,61,67).…”
Section: Increased Somatic Sensitivity After Rvssupporting
confidence: 80%
“…Similarly, increases in peripheral sensitivity to mechanical stimuli using von Frey filament application to the hindpaw are seen following CYP-induced cystitis in rodents (73). Therefore, increases in hindpaw and pelvic referred somatic sensitivity in the present study are similar to results seen in animal models of IC/BPS (45,61,67).…”
Section: Increased Somatic Sensitivity After Rvssupporting
confidence: 80%
“…Stimulus-related retraction of the tested paw was considered a withdrawal response, and the 50% paw withdrawal threshold was determined by the nonparametric method of Dixon (10). Previous studies have reported enhanced mechanical sensitivity of both the hind paws and pelvic region of mice in experimental cystitis (48,66,74) and similar results are reported, regardless of the area tested (48,66).…”
Section: Methodsmentioning
confidence: 82%
“…the ureter control the flow of urine into the terminal portion of the digestive tract (29,30) in a manner analogous to the VPAC2R + detrusor muscle of the mammalian bladder. Abnormal fluid regulation has also been described in mice lacking VIP or PACAP (40,42,43), so it will be of interest to establish if PDF signaling has related in vivo roles in flies. The presence of VIP/PACAP immunoreactivity in neural fibers of the lower urinary tract of mammals suggests a local, transmitter-like action on the excretory muscle receptors (12), and VIP is generally believed to act as a local neurotransmitter rather than as a circulating hormone (44,45).…”
Section: (D and E) Pdfr Expression In Adult Oregon-r Ureters (Arrows)mentioning
confidence: 99%